2022
DOI: 10.1158/1535-7163.mct-21-0860
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Experimental Gastric Cancer Activity of Irinotecan through Liposomal Formulation and Antiangiogenic Combination Therapy

Abstract: Gastric adenocarcinoma (GAC) is the third most common cause of cancer-related deaths worldwide. Combination chemotherapy remains the standard treatment for advanced GAC. Liposomal irinotecan (nal-IRI) has improved pharmacokinetics (PK) and drug biodistribution compared with irinotecan (IRI, CPT-11). Angiogenesis plays a crucial role in the progression and metastasis of GAC. We evaluated the antitumor efficacy of nal-IRI in combination with novel antiangiogenic agents in GAC mouse models. Animal survival studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Peritoneal metastasis is the most frequent form of metastasis in advanced GAC, and it is associated with poor prognosis ( 37 , 38 ). We established two peritoneal dissemination xenograft models using human MKN-45 cells and KATO-III cells that closely resemble the clinical GAC progression pattern ( 39 ). Nintedanib exhibited noticeable improvement in animal survival in these two models, which was much higher in KATO-III xenografts compared with MKN-45 xenografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal metastasis is the most frequent form of metastasis in advanced GAC, and it is associated with poor prognosis ( 37 , 38 ). We established two peritoneal dissemination xenograft models using human MKN-45 cells and KATO-III cells that closely resemble the clinical GAC progression pattern ( 39 ). Nintedanib exhibited noticeable improvement in animal survival in these two models, which was much higher in KATO-III xenografts compared with MKN-45 xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a meta-analysis of randomized controlled trials showed significantly improved survival and anti-tumor activity with the combination of multitarget antiangiogenic agents and taxane-containing chemotherapy in advanced NSCLC ( 42 ). Further, the combination of irinotecan with multitarget antiangiogenic drugs has been shown to have a synergistic antitumor response in gastric cancer and colorectal cancer models ( 39 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median OS of GAC patients receiving secondline therapy ranges from 3.6 to 10.9 months [112,129,130]. In GAC preclinical models, Awasthi et al recently demonstrated that nab-paclitaxel and liposomal irinotecan (nal-IRI) have higher anti-tumor efficacy than their solvent-based formulations [131][132][133][134][135]. Due to the low response rates of current standard therapies, and the development of chemoresistance and toxicity [136], several clinical studies evaluated nab-paclitaxel in GAC (Table 2).…”
Section: Nab-paclitaxel In Gastric Cancermentioning
confidence: 99%